Fabrication of schizophyllan hydrogel via orthogonal thiol-ene photopolymerization. (1st July 2017) - Lee, Sora; Tae, Hyunhyuk; Ki, Chang Seok
Highlights: SPG and PEG/SPG hydrogel fabrication via orthogonal thiol-ene reaction. The properties of SPG-based hydrogel could be modulated by controlling components. Mechanical enhancement of hydrogel has been achieved by dual mode crosslinking. Abstract: Schizophyllan (SPG) is a water soluble β-glucan, which is obtained from Schizophyllum commune . SPG has been widely explored with its unique properties such as triple helical structure, immune-modulation, and anti-tumoral activity. In this study, we tried to fabricate SPG hydrogel via thiol-ene photopolymerization. SPG-norbornene and SPG-thiol were synthesized from ultrasonicated SPG. Two types of SPG hydrogels (SPG and PEG/SPG hybrid) were formed via thiol-ene photo-click reaction. By controlling the SPG content and stoichiometric balance of norbornene and thiol groups, swelling ratio and shear elastic modulus of SPG hydrogel could be controlled in the range of 20–60 and 0.5–10 kPa, respectively. For PEG/SPG hybrid hydrogel, we found that the triple-helical structure of SPG played a role in physical network formation with thiol-ene cross-linking. The degradability of SPG hydrogel could be also modulated by varying formulation. Therefore, such highly tunable SPG hydrogels would be utilized for various applications.